2018
DOI: 10.3389/fpsyg.2018.00117
|View full text |Cite
|
Sign up to set email alerts
|

Monolingual and Bilingual Infants’ Ability to Use Non-native Tone for Word Learning Deteriorates by the Second Year After Birth

Abstract: Previous studies reported a non-native word learning advantage for bilingual infants at around 18 months. We investigated developmental changes in infant interpretation of sounds that aid in object mapping. Dutch monolingual and bilingual (exposed to Dutch and a second non-tone-language) infants’ word learning ability was examined on two novel label–object pairings using syllables differing in Mandarin tones as labels (flat vs. falling). Infants aged 14–15 months, regardless of language backgrounds, were sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 117 publications
3
17
0
Order By: Relevance
“…For example, Hay and colleagues tested 14‐, 17‐ and 19‐month‐old monolingual English‐learning infants with word–object mappings differing by Mandarin lexical tone contrasts (Hay et al., ). Work within the habituation Switch paradigm revealed that young 14‐month‐old infants succeeded in the task, whereas older, 17‐ and 19‐month‐old infants failed (see also Liu & Kager, , claiming a similar perceptual narrowing process for tone in monolingual Dutch infants). Singh and colleagues employed a visual choice paradigm to address a similar question (Singh et al., ).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…For example, Hay and colleagues tested 14‐, 17‐ and 19‐month‐old monolingual English‐learning infants with word–object mappings differing by Mandarin lexical tone contrasts (Hay et al., ). Work within the habituation Switch paradigm revealed that young 14‐month‐old infants succeeded in the task, whereas older, 17‐ and 19‐month‐old infants failed (see also Liu & Kager, , claiming a similar perceptual narrowing process for tone in monolingual Dutch infants). Singh and colleagues employed a visual choice paradigm to address a similar question (Singh et al., ).…”
Section: Discussionmentioning
confidence: 98%
“…Surprisingly, native tone‐language learners failed to use tones to learn words at around 12–13 months of age (Singh et al., ) although English‐ or Dutch‐learning 14‐month‐old infants, for whom tone distinctions are non‐native, succeeded in the task (Hay et al., ; Liu & Kager, ). What makes non‐native infants at this age outperform native infants?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations